Impact of Covid-19 cases on Global Stock Market - FRANCIS, FIONA SHEENU; KUMAR, DR. V. AMBILI (The journal of contemporary issues in business and government, 2021)
The current research tries to analyze the impact of the Covid-19 event and related deaths on the GLOBAL equity market (Dow Jones and the S&P500 indices), which compensate for trading volume and predictions of volatility, as well as the results on the weekday. Based on the GARCH(1) model and data from 8 April 2019 to 9 April 2020, the findings indicate that most affected countries with covid-19 crisis did not affect the stock market income. Nonetheless, the conditional heteroscedasticity of the Dow Jones and S&P500 returns in certain countries is having a positive effect. VAR models say that in Italy and France the number of deaths registered has a positive effect on the VIX returns. Finally, Markov-Stitching models show that the scale of VIX's negative effect on stock market prices increased threefold by the end of February 2020.